Ceiling-fan-integrated air conditioning: Airflow and temperature characteristics of a sidewall-supply jet interacting with a ceiling fan. (15th March 2020) - Chen, Wenhua; Zhang, Hui; Arens, Edward; Luo, Maohui; Wang, Zi; Jin, Ling; Liu, Junjie; Bauman, Fred S.; Raftery, Paul
Abstract: Ceiling-Fan-Integrated Air Conditioning (CFIAC) is a proposed system that can greatly increase buildings' cooling efficiency. In it, terminal supply ducts and diffusers are replaced by vents/nozzles, jetting supply air toward ceiling fans that serve to mix and distribute it within the room. Because of the fans' air movement, the system provides comfort at higher room temperatures than in conventional commercial/institutional/retail HVAC. We have experimentally evaluated CFIAC in a test room. This paper covers the distributions of air-speed, temperature, and calculated comfort level throughout the room. Two subsequent papers report tests of human subject comfort and ventilation effectiveness in the same experimental conditions. The room's supply air emerged from a high-sidewall vent directed toward a ceiling fan on the jet centerline; we also tested this same jet on a fan located off to the side of the jet. Primary variables are: ceiling fan flow volumes in downward and upward directions, supply air volume, and room-vs-supply temperature difference. Velocity, turbulence, and temperature distributions are presented for vertical and horizontal transects of the room. The occupied zone is then evaluated for velocity and temperature non-uniformity, and for comfort as predicted by the ASHRAE Standard 55 elevated air speed method. We show that temperatures are well-mixed and uniform across the room for all of the fan-on configurations, for fans both within or out of the supply jet centerline. The ceiling fan flow dominates the CFIAC airflow, and even though non-uniform is capable of providing comfortable conditions throughout the occupied area of the room. Highlights: A new air-conditioning concept CFIAC was first proposed and discussed. Airflow and temperature characteristics of CFIAC was studied. Thermal comfort of CFIAC was determined by ASHRAE procedure. Temperatures are well-mixed across the room for all of the fan-on configurations. Upward fan flow produces a more uniform air speed throughout the occupied zone.